THE RELATIONSHIP OF KNOWLEDGE OF POST PARTUM MOTHERS ON BREASTFEEDING TECHNIQUES WITH THE OCCUPATION OF BREAST MILK DAMS IN THE WORK AREA OF THE HEALTH CENTER, BUILDING AJI, TULANG BAWANG REGENCY - Neneng Siti Lathifah; Rosmiyati Rosmiyati; Fijri Rachmawati (ANJANI Journal (Medical Science & Healthcare Studies), 2022)
The local health office managed to collect data on postpartum women, including postpartum women, including 3000 physiological postpartum women, and postpartum women with problems, including 60 postpartum women who experienced uterine atony, 445 people. experienced breast milk dams, 4112 postpartum women experienced bleeding, 150 postpartum women experienced uterine involution, 100 postpartum women experienced dizziness, 25 postpartum women experienced an increase in body temperature and 266 postpartum women experienced mastitis. Based on the data from the Preliminary Study that I did at BPM Diana Ariyanti, I got data for the period May - August 2020, it was found that there were 19 postpartum mothers who experienced breast milk dams and for the period September - December 2020, 32 postpartum mothers received and who experienced breast milk dams. as many as 21 breastfed people. The purpose of this study is to determine the relationship between postpartum mother's knowledge about breastfeeding techniques and the occurrence of breast milk dams in the Working Area of the Aji Building Health Center, Tulang Bawang Regency in 2021.This type of research is quantitative. This type of research is descriptive correlation with the aim of knowing the relationship between one variable and another by using a cross sectional design. In this study, the number of samples to be taken were 32 respondents from postpartum mothers, total population technique. Analysis of univariate and bivariate data using chi square.good knowledge as many as 14 people (43.8%), and poor knowledge as many as 18 (56.2%). 15 respondents (46.9%) did not experience breast milk dam, and 17 respondents (53.1%) had breast milk dam. The results of the study obtained a p-value of 0.005 (0.05), which means that there is a relationship between postpartum mother's knowledge about breastfeeding techniques and the occurrence of breast milk dams in the Working Area of the Puskesmas Gedung Aji, Tulang Bawang Regency in 2021, with an Odds Ratio of 12.833 which means that the respondents' knowledge is not good. will be 13 times at risk of experiencing breast milk dam. It is hoped that the results of this study can be used as input for and improvement of programs related to the implementation of prevention of breast milk dams in their respective Puskesmas Working Areas. In addition, increasing exposure can also be done by presenting PPT or leaflets related to the handling and prevention of breast milk dams